2023
DOI: 10.1101/2023.03.09.531888
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative analysis of syngeneic mouse models of high-grade serous ovarian cancer

Abstract: Ovarian cancers often exhibit high rates of recurrence and poor treatment response. Preclinical models that recapitulate the heterogeneity of human disease are critical to develop new therapeutic approaches. While patient-derived models are a powerful tool for testing various therapeutics, their dependence on immune-compromised mice is severely limiting. Syngeneic mouse models, however, allow for the generation of tumours comprising the full repertoire of non-malignant cell types. Here we have performed a comp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 47 publications
(64 reference statements)
0
0
0
Order By: Relevance
“…However, ID8, and other OSEderived models, such as STOSE 78 , can recapitulate the dominant features of HGSC, namely peritoneal dissemination and omental metastasis. However, it has been shown that different murine models represent the HGSC tumour microenvironment differently, as recently demonstrated 79 . For this reason, we attempted to replicate our findings using the fallopian-derived HGS2 line 24 .…”
Section: Discussionmentioning
confidence: 86%
“…However, ID8, and other OSEderived models, such as STOSE 78 , can recapitulate the dominant features of HGSC, namely peritoneal dissemination and omental metastasis. However, it has been shown that different murine models represent the HGSC tumour microenvironment differently, as recently demonstrated 79 . For this reason, we attempted to replicate our findings using the fallopian-derived HGS2 line 24 .…”
Section: Discussionmentioning
confidence: 86%
“…Despite an equivalent amount of DNA damage, the ID8 Trp53 −/− Brca2 −/− cells were the more olaparib-sensitive cell line, with viability reduced significantly at every dose of olaparib tested. Since olaparib differently affected Brcanull cell viability, the expression of genes associated with the PARP pathway in the ID8 cell lines was compared by querying RNA-seq data previously published in our lab [23]. We discovered that the ID8 Trp53 −/− Brca2 −/− cells growing in vitro demonstrated a higher expression of both PARP1 and PARP2 compared to the Brca1 −/− model (Fig.…”
Section: Olaparib Increases Dna Damage and Reduces Viability In Brca-...mentioning
confidence: 95%
“…As the TME analysis from the two models revealed differences in various cell populations and cytokines, we analyzed previously published bulk RNA sequencing data [23] from both Brca-deficient IP tumour models to further investigate the differences between them. The analysis revealed notable differences in the transcript levels of several cell type markers in Brca-null TMEs.…”
Section: Depletion Of Brca1 and Brca2 In Ovarian Cancer Cells Differe...mentioning
confidence: 99%
See 2 more Smart Citations